KESIAPAN KARYAWAN DALAM MENGHADAPI TRANSFORMASI DIGITAL: A SYSTEMATIC. (LITERATURE REVIEW STRATEGI DAN TANTANGAN MANAJEMEN SUMBER DAYA MANUSIA) - Rahmah, Salsabila Zulfa; Milad, Mohammad Khusnu (Growth, 2025)
The advancement of digital technology has significantly transformed how organizations manage human resources (HR). This study aims to examine employee readiness in digital transformation by focusing on psychological, technical, and organizational aspects. A systematic literature review of 25 national and international journals 2020 until 2025 was conducted using content analysis. The results show that readiness depends not only on digital skills but also on psychological factors such as confidence and openness to change, supported by leadership, training, and flexible structures. Challenges include resistance to change, low digital literacy, and rigid bureaucracy in public institutions. The study emphasizes the importance of digital leadership and adaptive learning systems to strengthen transformation. Theoretically, this research expands HR readiness discourse by combining technical and cultural perspectives. Practically, it guides organizations in creating strategies that integrate technology adoption with human-centered approaches to ensure sustainable transformation. Keywords: digital transformation, employee readiness, human resources, digital leadership, organizational change